2017
DOI: 10.20944/preprints201704.0135.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of G Protein-Coupled Receptors by Ubiquitination

Abstract: G protein-coupled receptors (GPCRs) comprise the largest family of membrane receptors that control many cellular processes and consequently often serve as drug targets. These receptors undergo a strict regulation by mechanisms such as internalization and desensitization, which are strongly influenced by posttranslational modifications. Ubiquitination is a posttranslational modification with a broad range of functions that is currently gaining increased appreciation as a regulator of GPCR activity. The role of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…11 We disregard that MAS1R endocytosis, through caveolae, may be coupled to degradation because we showed that MAS1R expression was not modified and it was not targeted to the lysosomes after 60 min of agonist stimulation (Figure 3). Some GPCRs are often directed for lysosomal degradation via the conserved endosomal-sorting complex required for the transport machinery, but others are directed to the resensitization pathway 28 , as occurs with the MAS1R (the current results). Other GPCRs, such as the metabotropic glutamate receptors 1 and 5, the human follitropin receptor, different opioid receptors, acetylcholine receptors, or glycine receptors, undergo basal and agonist-induced proteasomal degradation.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…11 We disregard that MAS1R endocytosis, through caveolae, may be coupled to degradation because we showed that MAS1R expression was not modified and it was not targeted to the lysosomes after 60 min of agonist stimulation (Figure 3). Some GPCRs are often directed for lysosomal degradation via the conserved endosomal-sorting complex required for the transport machinery, but others are directed to the resensitization pathway 28 , as occurs with the MAS1R (the current results). Other GPCRs, such as the metabotropic glutamate receptors 1 and 5, the human follitropin receptor, different opioid receptors, acetylcholine receptors, or glycine receptors, undergo basal and agonist-induced proteasomal degradation.…”
Section: Discussionmentioning
confidence: 64%
“…Other GPCRs, such as the metabotropic glutamate receptors 1 and 5, the human follitropin receptor, different opioid receptors, acetylcholine receptors, or glycine receptors, undergo basal and agonist-induced proteasomal degradation. 28, 29 For instance, the AT 1 R is directed to lysosomes, but it is also recycled back to the plasma membrane by both slow and rapid recycling vesicles, and when it is heterodimerized with the dopamine receptor D 5 R, it targets to proteasomes for degradation, with the half-life of the AT1R approximately 150 min. 30 Thus, R trafficking is specific for each R. Certainly, at some stage, a fraction of the MAS1Rs may be directed to lysosomes or proteasomes for degradation, but at the time interval assayed in the present study (no more than 60 min), the MAS1R was mostly recycled back to plasma membrane and not a significant amount of the MAS1R was detected in the lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive evidence shows that multiple GPCRs, including the β 2 -2 adrenergic receptor (β2AR), PAR1 and PAR2 proteaseactivated receptors, µ-and δ-opioid receptors, CXCR chemokine receptors, V2R vasopressin receptor, D4 dopamine receptor, and PTHR (14) are ubiquitinated by covalent addition of ubiquitin to intracellular lysines (Lys). Ubiquitination regulates internalization and trafficking of these receptors, often targeting receptor protein for degradation, either in an agonist-dependent or -independent manner (15).…”
mentioning
confidence: 99%
“…G protein‐coupled receptors that undergo agonist‐induced ubiquitination are usually internalized and targeted for degradation in lysosomes. However, after deubiquitination they can be redirected to the resensitization pathway and recycled back to the cell surface . The addition of a single ubiquitin to a substrate is defined as monoubiquitination and is implicated in various functions including endocytosis of plasma membrane proteins and sorting of proteins to the multivesicular body .…”
Section: Discussionmentioning
confidence: 99%